COVID-19 Vaccination Among the Arab Bedouin Population: Lessons Learned From a Minority Population - Naim Abu-Freha; Naim Abu-Freha; Naim Abu-Freha; Hadel Alsana; Hadel Alsana; Sabri El-Saied; Sabri El-Saied; Zuya Azbarga; Muhammad Aloka; Tarek Goda; Muhammad Abu Tailakh; Muhammad Abu Tailakh (Frontiers Media S.A., 2022)
Objectives: We investigated the causes of low COVID-19 vaccination rates among a minority population and highlighted interventions for increasing the vaccination rate.Methods: We reviewed the experience during the mass vaccination campaign period among the Arab Bedouin (AB) in Israel, attempting to determine important causes of low vaccination rates and gathered information from real-life experience and through direct contact with the population during the campaign.Results: Causes for low vaccination rates in the AB are related to the health system infrastructure, crisis management strategies, and population characteristics. Long-standing socioeconomic inequalities, limited resources, and language and culture barriers present special challenges to the task of COVID-19 vaccination campaigns. Key interventions for increasing vaccination rates among minority populations include raising awareness, improving vaccination access, and directly targeting risk-groups. To maximize the effectiveness of these interventions they should be culturally adapted and executed according to the needs of each individual target community.Conclusion: Culturally adapted awareness campaigns, interventions, and improved access to vaccines can be accomplished by cooperation between relevant governing and community bodies to increase COVID-19 vaccination rates among minorities.